Sitting or standing: Effects on sustained attention of sleep deprived students - Brant, Valdenio Martins; Silva, Andressa; Andrade, Henrique Araújo; Narciso, Fernanda Veruska; Morais, Juliana Karine Santos; Lobo, Ingrid Ludmila Bastos; Guerreiro, Renato Carvalho; Mello, Marco Túlio de (Journal of Physical Education (Maringá), 2025)
Introduction: During sleep deprivation, sustained attention is impacted by homeostatic pressure to sleep and the number of tasks. Objective: to compare the effects of 36h of sleep deprivation on psychomotor performance during a Single-Task Condition (STC) vs Dual-Task Condition (DTC) in university students. Method: During 36 hours of sleep deprivation, the Psychomotor Vigilance Task (PVT) was applied to 13 male university students, in the STC and DTC situations, sitting in a chair or standing on a force platform, every 3 hours, totaling 13 evaluations, from 08am on day 1 to 08pm on day 2. Results: There was an effect of time on the STC and DTC in all 13 evaluation moments, in all variables analyzed, except Mean RT and Slowest 10% RT, for a p-value of 0.05. No significant difference was found in the PVT variables in the comparison between the two conditions, despite a trend to significance, in the moments of homeostatic pressure to sleep in the task (05am and 02pm on day 2). Conclusion: Sleep deprivation negatively affected the psychomotor performance of participants in both conditions, demonstrating worsening of sustained attention, greater engagement of standing posture and revealing greater relaxation of sitting posture.